Immunoglobulin Rapid Test Sensitivity in PCR-Positive COVID-19 Patients - Ahmad A. Alharbi; Mohammad K. Alshomrani; Abdullah A. Alharbi; Abdulrahman H. Almaeen; Saad AlAsiri; Awad Al-Omari; Imad Alishat; Saeed Dolgom (Dr. Sulaiman Al Habib Medical Journal, 2022)
Abstract Background Diagnostic assays aimed at the identification of immunoglobulin G (IgG) and immunoglobulin M (IgM) offer a rapid and adjunct modality to conventional real-time reverse transcription polymerase chain reaction (rRT-PCR) assays for the diagnosis of coronavirus disease 2019 (COVID-19). Aim To analyze the sensitivity of IgG and IgM-based serological assays in rRT-PCR-positive COVID-19 subjects. Methods A consecutive cohort of 69 patients with COVID-19-related symptoms or recent exposure to COVID-19-positive individuals were included after taking informed consent. Nasopharyngeal swabs for SARS-CoV-2 rRT-PCR analysis and venous blood samples for the COVID-19 IgG/IgM rapid test were simultaneously collected from each subject on day 0. Then, in the case of positive PCR results, subsequent blood samples for COVID-19 IgG/IgM analysis were collected on days 7, 10 and 14. Samples were statistically analyzed to determine the sensitivity of the serology-based assays. Results No correlation was found between age or sex and the rRT-PCR, IgG and IgM results; 65.2% of subjects tested positive by rRT-PCR. The sensitivity of the IgM and IgG rapid test increased gradually with time, reaching the highest level on day 14 (22.2% and 72%, respectively). Conclusion Serological assays for the detection of infection with SARS-CoV-2 were compared to rRT-PCR. These assays yielded lower sensitivities than rRT-PCR-based assays. However, given that these immunoassays are more affordable, faster, and easier to execute, they could be recommended for epidemiological research or characterizing the immune status of post-infection or post-vaccination subjects.